Personal Branding Arief Budiman sebagai Foodgram Dalam Akun Instagram @kulineryogya - Brian Taufiqurrahman; Fajar Junaedi (President University, 2022)
Arief Budiman is a foodgram and successfully built his personal branding behind Instagram account @kulineryogya. The purpose of this study is to find out Arief Budiman's personal branding model as a foodgram in the @kulineryogya Instagram account. This research is a case study. The post-positivism paradigm is used by researchers and also qualitative description method with data collection techniques in the form of documentation and interviews. Arief Budiman applies the concept of The Eight Laws of Personal Branding in @kulineryogya's Instagram content, which is able to communicate his concept to citizens through Instagram based on a strong specialization developed with credibility, making Arief Budiman able to show his competence in various matters regarding fields related to culinary. Its credibility is presented to the audience with a friendly personal approach. Friendliness in interacting with netizens is an important key to building personal branding on social media. This model is done by building interactions with his followers on social media. This shows that personal branding on Instagram social media must be carried out with an interactive communication approach. Interactivity is developed not only on social media but also by being actively involved in offline events. This personal branding model on Instagram social media is a unity that is intertwined.